2016
DOI: 10.1007/s11192-016-1854-0
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of nanotechnology knowledge in Turkey and its network structure

Abstract: This paper aims to assess the diffusion and adoption of nanotechnology knowledge within the Turkish scientific community using social network analysis (SNA) and bibliometrics. We retrieved a total of 10,062 records of nanotechnology papers authored by Turkish researchers between 2000 and 2011 from Web of Science (WoS) and divided the data set into two 6-year periods. We analyzed the most prolific and collaborative authors and universities on individual, institutional and international levels based on their net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…12 Bibliometrics is defined as the application of mathematics and statistical methods to communication media. Bibliometrics have been used extensively to evaluate research progress quantitatively, for example in studying research output for specific countries [13][14][15] in a continent or a region such as Africa or southern Africa 16,17 or sometimes for a research discipline such as nanotechnology 9,18 or even a single institution 19 . One problem identified in bibliometric research is the classification and delineation of fields, for example, for new and emerging areas like biotechnology and nanotechnology the definitions differ among different application areas, including which areas it encompasses.…”
Section: Bibliometricsmentioning
confidence: 99%
“…12 Bibliometrics is defined as the application of mathematics and statistical methods to communication media. Bibliometrics have been used extensively to evaluate research progress quantitatively, for example in studying research output for specific countries [13][14][15] in a continent or a region such as Africa or southern Africa 16,17 or sometimes for a research discipline such as nanotechnology 9,18 or even a single institution 19 . One problem identified in bibliometric research is the classification and delineation of fields, for example, for new and emerging areas like biotechnology and nanotechnology the definitions differ among different application areas, including which areas it encompasses.…”
Section: Bibliometricsmentioning
confidence: 99%
“…Some scholars based their work on the perspective of influencing factors to study the influence of knowledge diffusion in a network. For example, the regression analyses of Xie et al [9] and Darvish [10] found that network structure indexes such as network scale and connection strength have a positive impact on knowledge diffusion. Chen et al [11] , Mao et al [12] and Havakhor et al [13] conducted simulation analyses and found that the main ability, spatial relevance and knowledge role distribution of a network have an important impact on the knowledge diffusion process.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many efforts to characterize the nature of knowledge flow from multiple perspectives of detail, namely: among scientists [6,7], among patents [3,8], among patents and journals [9][10][11], among journals [12][13][14], among disciplines [15,16], among institutions [17], and among countries [18][19][20], etc. The prior researches provide a comprehensive understanding of the nature of knowledge flow; in particular, enrich the potential utility of analyzing its processes.…”
Section: Introductionmentioning
confidence: 99%
“…Social network can establish connections among researchers and plays a facilitative part in enhancing knowledge flow [14,23]. Social network analysis is a powerful means to investigate the interactions and patterns of knowledge flows among group members [20]. Identifying the significance of nodes in the network is a classical topic in the field of informetrics [7,24,25].…”
Section: Introductionmentioning
confidence: 99%